The Effectiveness of the Difference in the Playing Method of Stilt Batok and the Dingklik Relay on the Improvement of Gross Motor Skills and Balance in Deaf Children - Teddy Giolanda Pratama; Subagyo Subagyo; Ngatman Ngatman; Muhamad Ichsan Sabillah; Abiyyu Amajida; Achad Imam Ma’ruf; Vistor Syapri Maulana (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introducción: El problema en este estudio es la baja Motricidad Gruesa y Equilibrio en Niños Sordos.